Effectiveness of treatment regimens for Typhoid fever in the nalidixic acid-resistant S. typhi (NARST) era in South India. (July 2018) - Bandyopadhyay, Rini; Balaji, Veeraghavan; Yadav, Bijesh; Jasmine, Sudha; Sathyendra, Sowmya; Rupali, Priscilla
The epidemiology of typhoid fever in South Asia has changed. Multi-drug resistant (MDR) Salmonella typhi ( S. typhi ) is now frequently resistant to nalidixic acid and thus labelled NARST. Treatment failure with the use of fluoroquinolones has been widely noted, forcing clinicians to adopt alternative treatment strategies. In this observational study, we looked at various treatment regimens and correlated clinical and microbiological outcomes. In 146 hospitalised adults, the median minimum inhibitory concentration (MIC) for ciprofloxacin was 0.38 µg/mL with a median fever clearance time (FCT) of eight days (range = 2–35 days). Of the regimens used, gatifloxacin and azithromycin had a shorter FCT of six days compared to ceftriaxone (ten days; P  < 0.001). Though mortality and relapse in our cohort was low, NARST seemed to correlate with mortality ( P  = 0.006). Gatifloxacin or azithromycin clearly emerge as the drugs of choice for treatment of typhoid in South India.